2006
DOI: 10.1248/bpb.29.1290
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Condensed DNA by Liposomal Non-viral Gene Delivery System into Nucleus of Dendritic Cells

Abstract: In general, foreign substances can not enter the nucleus of non-dividing cells, in which nuclear membrane does not disappear by cell division, since nuclear transfer is strictly controlled by precise machinery. For example, nuclear proteins are recognized by importin a in the cytoplasm with a nuclear localization signal (NLS) attached to the nuclear proteins, and importin b then combines with the NLS/importin a. The complex binds to the nuclear pore complex (NPC), and passes through the NPC into nucleus. 1) Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…We used STR-NLS since, in a previous study, we demonstrated that modification of STR-NLS on the surface of liposomes enhanced the gene expression of encapsulated pDNA in primary dendritic cells. 10) Although DSPE-NLS may be more useful in comparing the effect of the PEG spacer, it is plausible that almost all of the STR-NLS and DSPE-PEG-NLS were stably incorporated in the lipid envelope since STR-NLS and DSPE-PEG-NLS were incorporated when lipid film was formed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used STR-NLS since, in a previous study, we demonstrated that modification of STR-NLS on the surface of liposomes enhanced the gene expression of encapsulated pDNA in primary dendritic cells. 10) Although DSPE-NLS may be more useful in comparing the effect of the PEG spacer, it is plausible that almost all of the STR-NLS and DSPE-PEG-NLS were stably incorporated in the lipid envelope since STR-NLS and DSPE-PEG-NLS were incorporated when lipid film was formed.…”
Section: Resultsmentioning
confidence: 99%
“…Stearyl NLS (STR-NLS) was synthesized as described previously. 10) JAWS II cells derived from murine dendritic cells were purchased from the American Type Culture Collection (Manassas, VA, U.S.A.). Other chemicals used were commercially available and were reagent grade products.…”
Section: Egg York Phosphatidylcholine (Epcmentioning
confidence: 99%
See 1 more Smart Citation
“…20) In this method, PGA/ Dox is mixed with SUVs, and encapsulation of PGA/Dox results from membrane fusion of SUVs around the PGA/Dox complexes. When PGA/Dox was mixed with SUVs (10 mM DOPE : DCP=9 : 2), the particle sizes of the resulting liposomes were found to be smaller than that of PGA/Dox alone (Table 3), which may be due to tight packing of PGA/Dox by the lipid membrane.…”
Section: : 1 Aggregatedmentioning
confidence: 99%
“…Thus, as a third strategy, we modified the NLS or sugars (i.e. maltotripse) that can target nucleus on the envelope structure of the MEND by inserting a lipid derivative of a NLS [64,65]. This design permits the the NLS peptide to be spontaneously oriented in an outward direction from the particle surface.…”
Section: Control Of the Intracellular Trafficking For Pdna Deliverymentioning
confidence: 99%